Cacooney / Husnie Shahriza Shari … [et al.] - Shari, Husnie Shahriza; Badioezaman, Nur Amirah Filzah; Wan Muhammad Saberi, Wan Halimaatun Nurul Ashikin; Mohd Nazri, Nor Adilla; Ahmad Nizar, Nurul Izzati (Research Innovation Business Unit, 2014)
Most people spend up to 6 to 9 hours per day in bed, and are exposed to the mattresses, pillows and bedding for a considerably length of time. These items touch our skin and some may release chemicals and fumes that we would breathe for several hours at a time. Of all the items we surround ourselves with during a single 24-hour period; our mattress may have the largest surface area contact with our physical self. Cacoon mattress! Cacoon mattress is a three-layer mattress that consists of organic cotton, water and air. A mattress which is really comfortable, affordable, compact, lightweight, convenient should be good for our health! Cacoon mattress is designed to overcome roughness, sleeping hardness and discomfort. You can wrap yourself with Cacoon mattress to feel warm and comfortable during sleep. You will also feel protected! Cacoon mattress is easy to store and always ready for immediate use. It is also portable and handy. The three main categories of usage are camping outdoors, temporary home use for the guests and full time or permanent use in the bedroom. Cacoon mattress also comes in different colours and is good for our health? This is because; Cacoon mattress is made out of organic cotton, water and air. The first layer is organic cotton mattress. Organic cotton is grown in farms that are pesticide-free, using methods and materials that have low impact on the environment. Organic cotton mattress is hypoallergenic, which reduces the risks of allergies and asthma. Because there are no irritating chemicals used in their growth and production, none of these toxics will end up in your bed or on your body. Moreover, natural organic cotton used in this mattress can increase comfort. Cotton’s breathability also allows it to absorb and release moisture without feeling damp, helpful in keeping you comfortable throughout the night. The second layer of Cacoon mattress is water. Water mattress offer sleepers the ability to truly relax and stop shifting their position at night. It is proven that water mattress can reduce back problems. Water mattresses removes pressure from the spine and allow relaxation of spinal musculature and enables the backache sufferer to sleep in a more comfortable and relaxed position. A unique distribution of support for the body assures that all parts of the body are evenly supported, and that the body weight is equally distributed. Besides that, water mattress offers sleepers the ability to regulate the temperature of their bed. Water inside mattress allows sleepers to feel as if they are floating. They can remove or add in water to control the temperature to feel comfortable. The third layer of Cacoon mattress is air. The greatest advantage of an air mattress is that it provides the opportunity of adjusting the firmness of the surface, as per your requirement. This leads to a good night’s sleep and overall improved health. These are the health benefits of the Cacoon mattress.